Smart home and communication technology for people with disability: a scoping review. - Jamwal, Rebecca; Jarman, Hannah K.; Roseingrave, Eve; Douglas, Jacinta; Winkler, Dianne (Disability & Rehabilitation: Assistive Technology, 2022)
The links between disability, activity limitation and participation restriction are well established. Recent and continued advancement of technology, particularly smart home and communication technologies, presents new ways in which some of the limitations and restrictions experienced by people with disabilities can be overcome. The aim of this scoping review was to explore the impact of smart home and communication technology on the outcomes of people with disabilities and complex needs. This review involved systematic searching of four databases, hand searches and data extraction. Eligibility criteria included [1] participant outcomes of [2] technology used within the home [3] among adults with a disability and complex needs. Of the 2400 studies identified, 21 met our inclusion criteria. Studies were characterized by significant diversity in relation to disability and type of technology. Overall, technology appeared to improve independence, participation and quality of life among people with a disability and complex needs. Despite this, ethical considerations were raised given the vulnerability of this population, including potential risks through social participation and privacy concerns of using monitoring technology. Smart home and communication technology can improve outcomes for people living with disabilities and complex needs. However, a number of factors impact the successful implementation of technology, including personalization, flexibility and ongoing support to the person with a disability and their close others. Future research should utilize high-quality study designs and established measures of important outcomes for this group. There is a broad range of smart home and communication technology devices and systems available that may support the independence and participation of people with disabilities and complex needs; however, high-quality evidence documenting the impact of technology is lacking. Soft-technology supports, including assessment, training and evaluation of technology implementation, may play just as important a role in shaping outcomes as the technology itself. Systematic research is required to ensure there is quality evidence to inform investment in both technologies, and the soft-technology supports that promote its successful use.